Improved Performance for the Electrochemical Sensing of Acyclovir by Using the rGO–TiO2–Au Nanocomposite-Modified Electrode - Lu, Xin-Yang; Li, Jing; Kong, Fen-Ying; Wei, Mei-Jie; Zhang, Pei; Li, Ying; Fang, Hai-Lin; Wang, Wei (Frontiers in Chemistry, 2022)
An electrochemical sensor for sensitive sensing of acyclovir (ACV) was designed by using the reduced graphene oxide-TiO2-Au nanocomposites modified glassy carbon electrode (rGO-TiO2-Au/GCE). Transmission electron microscopy, X-ray diffractometer and X-ray photoelectron spectroscopy were employed to confirm the morphology, structure and composition properties of the rGO-TiO2-Au nanocomposites. Cyclic voltammetry and linear sweep voltammetry were used to demonstrate the analytical performance of the rGO-TiO2-Au/GCE for ACV. As a result, rGO-TiO2-Au/GCE exerted the best response for the oxidation of ACV under the pH of 6.0 PB solution, accumulation time of 80 s at open-circuit, and modifier amount of 7 µL. The oxidation peak currents of ACV increased linearly with its concentration in the range of 1-100 µM and the detection limit was calculated to be 0.3 µM (S/N = 3). The determination of ACV concentrations in tablet samples also demonstrated satisfactory results.